(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2015)
Synthesis and design of new ligands are very important for selective uranium extraction from nuclear waste and for the determination of its microquantities. For this reason, we synthesized 3,3’-(2,2’-dyhydroxyphenyl)-di-1,2,4-triazole (H4L), as a model of 1,2,4-triazole containing ligands eligible for practical use, and coordination compound UO2(H2L)Solv as well. 3,3’-(2,2’-dyhydroxyphenyl)-di-1,2,4-triazole was obtained by acylation of malonic acid hydrazide with salicylic acid iminoester in methanol solution and following intermolecular cyclization of the acylamidrazone. Obtained ligand formed neutral coordination compound with uranyl ion UO2(H2L)Solv in metal to ligand molar ratio M:L = 1:1. Crystal and molecular structure of the UO2(H2L)Solv was determined by X-ray diffraction analysis. It was found that equatorial position of uranium are occupied by tetradentate coordinated ligand and one molecule of DMF. Coordination polyhedron of uranyl is a pentagonal bipyramid. Ligand comprised in complex as dianion (H2L2-) due to deprotonation of hydroxy groups, while triazole rings remaine in acidic form. Angle between planes of the phenyl and triazole rings is 21.5°, and angle between triazole heterocycles planes are 137°. The investigation of complex in solution was provided by means of NMR spectroscopy. Low-field shift of signals of protons H1, H2, H4 and hydrogen of triazole, strong-field shift of signal proton H3 in NMR spectra shows that UO2(H2L)is stable in dimethylsulfoxide solution.